In-vivo bone-borne expansion protocols with piezoelectric sutural corticotomy / Akram Shaker Hussein Alyessary - Akram Shaker, Hussein Alyessary (2018)
This study consisted of two phases. In phase one, the effect of accelerated bone-borne expansion protocols on sutural separation and new sutural bone formation were evaluated using micro-computed tomography, histomorphometry, and immunohistochemistry. The optimum instant sutural expansion possible without disruption of bone remodeling and formation was also determined. In phase two, the effects of piezoelectric sutural corticotomy on the amount of sutural separation and new suture bone formation with accelerated bone-borne sutural expansion were studied. Differences between continuous and discontinuous sutural corticotomy was also explored. Materials and Methods: In this study, sixteen 20 to 24-week old New Zealand white rabbits were randomly divided into 4 experimental groups for phase one. For phase two, 14 rabbits were randomly divided into 3 experimental groups. Modified hyrax expanders were placed across the midsagittal sutures of the rabbits and secured with miniscrew implants located bilaterally in the frontal bone. In phase one, the hyrax appliances were activated as follows: Group 1 (control), 0.5 mm/day expansion for 12 days; group 2, 1 mm instant expansion followed by 0.5 mm/day for 10 days; group 3, 2.5 mm instant expansion followed by 0.5 mm/day for 7 days, and group 4, 4 mm instant expansion followed by 0.5 mm/day for 4 days. In the phase two, the groups were as follows: Group 1, accelerated sutural expansion; group 2, accelerated sutural expansion with continuous corticotomy; and group 3, accelerated sutural expansion with discontinuous corticotomy. All sutural corticotomies were performed using a piezoelectric instrument prior to expander application under anesthesia. The hyrax expanders were activated 2.5 mm instant expansion followed by 0.5 mm/day for 7 days. After 6 weeks of retention, bone volume fraction, sutural separation, and new bone formation were evaluated using micro-computed tomography and histomorphometry/immunohistochemistry. Results: In phase one, the smallest median sutural separation was observed with group 1 (3.05 mm) and the greatest with group 4 (4.57 mm). The least and most bone formation was observed with group 4 (55.82%) and group 3 (66.93%), respectively. A significant correlation (r=0.95, p<0.01) was observed between the amount of instant expansion and sutural separation. In phase two, ranking of median sutural separation was as follows: Group 1 (3.97 mm), group 3 (4.97 mm) and group 2 (5.58 mm). The least and most bone formation were observed with groups 1 (66.93%) and 2 (76.25%), respectively. Spearman’s correlation showed strong, positive and significant correlation (r= 0.881, p<0.01) between the new sutural bone formation and amount of sutural separation. Conclusion: The sutural bone formation corresponded with the amount of instant expansion to a critical point beyond which the ability of the suture to remodel was disrupted. The protocol involving 2.5 mm instant expansion was the optimal for accelerated sutural expansion. When 4 mm instant expansion was employed, new suture bone formation was decreased. In addition, piezoelectric sutural corticotomies increased sutural separation and promoted new sutural bone formation. Continuous corticotomy gave better results than discontinuous corticotomy.